(untitled) (Journal of Economic Research & Business Administration, 2022)
This study investigated the trend of forward looking information disclosure among non-financial firms in Nigeria over the period of nine years that is, 2012 to 2020. The study employed secondary data which were obtained through content analysis of the financial statements of sampled non-financial firms. The population of the study consists of 115 non-financial firms listed on the Nigerian Stock Exchange as at 31st December, 2020. 50 firms were purposively sampled based on the availability of financial statement and listing age over the period examined by the study. The data were analysed using percentages and charts. The findings of the study revealed that based on the forward looking information disclosure index employed, Nigerian firms disclosure 35.49 percent forward looking information disclosure level over the nine year sampled with the year 2019 reflecting the highest level of forward looking information disclosure at 39.8 percent. The study concluded that although forward looking information disclosure had experienced a steady increase in disclosure levels over the sampled period, the level of forward looking information is relatively low to satisfy stakeholder needs and therefore recommends that management of firms in Nigeria should endeavour to improve forward looking information disclosure due to its importance to stakeholder’s decision making. Key words: Forward looking information disclosure, Forward Looking Information Index, Voluntary Disclosure, Corporate Reporting.